Rate of Change of Direct-Axis Current Component Protection Scheme for Inverter-Based Islanded Microgrids - Abdolhamid Farshadi; Behzad Keyvani Eydi; Hamed Nafisi; Hossein Askarian-Abyaneh; Arash Beiranvand (IEEE Access, 2023)
Rapid growth in the utilization of the inverter-interfaced distributed energy resources (IIDERs) in microgrids has brought new challenges in the network protection area. Microgrid protection specifically becomes a concern during operation in the islanded mode. There is a considerable reduction in fault current levels in this mode compared to when the microgrid is connected to the grid, which makes conventional algorithms operate with significant delay or, in many cases, not even pick up the fault. This paper proposes a protection algorithm based on the rate of change of direct-axis current component ( $i_{d}$ ) to protect inverter-based microgrids (IBMGs). The proposed algorithm is applicable for microgrids with centralized protection as well as those deploying a decentralized approach equipped with the unit protection of the relevant lines. Photovoltaic (PV) systems and battery energy storage systems (BESS) are taken into account in this research and modeled precisely to capture the high-frequency effects of power-electronic converters and investigate the response of IIDERs in fault conditions. The effectiveness of the proposed protection method will be evaluated by applying symmetrical and asymmetrical faults in different locations with different resistances simulated on a test IBMG system in PSCAD/EMTDC environment. In addition, protection robustness against non-fault conditions such as a sudden increase in load levels, environmental uncertainties, and noisy measurement conditions will be scrutinized.